Doubling down political budget cycles: The role of state-owned enterprises - Zareh Asatryan; Désirée I. Christofzik; Justus Nover (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2025)
We study the degree and nature of political budget cycles in public investments when two instruments are available: investments by core governments and, more indirectly, by state-owned enterprises (SOEs). While fiscal pressure on core budgets may induce politicians to shift election-induced investments to SOEs, voters' uncertainties in clearly attributing the benefits of SOE investments to incumbent politicians may encourage the opposite. Using administrative micro-data for over 10,500 SOEs and their public owners at the municipal level in Germany, we document substantial election cycles in both instruments. This suggests that German municipal councilors use investments broadly to enhance their re-election prospects. The total effect of elections on municipal investments in our sample is over EUR 1 billion for the pre-election year in each electoral cycle, while the past literature focusing only on core budgets would miss about a third of this effect.
Keywords: H11; L32; D72; 330; election cycles; core budgets; outsourcing; transparency